OPTIMAL TIMING FOR TEACHING CHILDREN A FOREIGN LANGUAGE (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
: This article explores the optimal age for introducing a foreign language to children, considering cognitive development, educational benefits, and societal implications